'Pasifika' and 'I‐Kiribati' identity in Aotearoa New Zealand: 'Dancing' and 'edge‐walking' through multiple identities. (5th November 2019) - Burnett, Roi; Bond, Sophie
Abstract : This article explores the relationship between I‐Kiribati communities and the broader 'imagined' Pasifika community in Aotearoa New Zealand. It looks at the way a group of I‐Kiribati tertiary students experience identity within this context. Through the use of semi‐structured interviews and a discourse analysis, the study draws three main conclusions. First, that I‐Kiribati navigate multiple identities and are constantly negotiating these within different spaces. Although this contributes to uncertainties around identity, I‐Kiribati students also strategically enact identity to suit various contexts. Second, that Pasifika as a term tends to infer 'Polynesian' which in turn may marginalise I‐Kiribati identities within certain spaces, particularly in education settings that intend to support all Pacific identities. Yet, given such a narrow understanding of Pasifika, these efforts may counter that intention for those on the margins of, or outside the common usage of, the term Pasifika. Last, community plays a significant role in the formation of identities within minority groups, which is important for countering aspects of marginalisation experienced within broader pan‐ethnic labels such as Pasifika. Consequently, we argue that Pasifika as a label needs to better reflect inter‐Pacific diversity as well as the identity negotiations that Aotearoa New Zealand‐born Pacific peoples navigate.